The Enhancement of the Vice President of Indonesia's Strategic Role and Constitutional Functions as Mandated by Article 4 of the 1945 Constitution - Zulbaidah, Zulbaidah (Faculty of Law, Universitas Pekalongan, 2025)
This study explores the constitutional position and authority of the Vice President within the framework of Indonesia’s presidential system, highlighting the persistent ambiguity and limited normative foundation of the office since the adoption of the 1945 Constitution and its subsequent amendments. Although Article 4(2) of the Constitution mentions that the President is assisted by a Vice President, it fails to define the division of responsibilities or to grant the Vice President independent public legal authority. As a result, the Vice President’s functions are largely contingent upon delegation from the President, leading to a dependency that undermines institutional clarity and effectiveness. The absence of detailed regulation creates a legal vacuum (recht vacuum) and contributes to inefficiencies in governance. In response, this paper proposes a comprehensive reformulation of the Vice President’s role and powers, including clearer constitutional authority, proportional task distribution, strengthened coordinative and representative functions, and the enactment of specific legislation governing the office. These reforms aim to reinforce the Vice President’s contribution to state administration, enhance legal certainty, and promote good governance. Ultimately, a well-structured and constitutionally grounded relationship between the President and Vice President is essential to the development of a more effective and integrated executive leadership in Indonesia.